Association of Vitamin D Deficiency with Acute Respiratory Tract Infection in Children of Peshawar (Medical Forum Monthly, 2022)
Objective: To identify the association of vitamin D levels on incidence of respiratory tract infection in children of Peshawar.Study Design: Observational studyPlace and Duration of Study: This study was conducted at the Paediatric Units of Mercy Teaching Hospital and Kuwait Teaching Hospital, Peshawar from 1st January 2020 to 31st July 2020.Materials and Methods: One hundred and ninety nine children were enrolled. All male and female children in current study were between 0 weeks to 5 years. The medical history of all participants was recorded in self-made questionnaire and blood sample was collected to identify the vitamin D levels. Participant had genetic inheriditry disease such as X linked rickets, hypophosphatemia rickets were excluded.Results: The baseline mean vitamin levels in healthy children were high 15±7 ng/mL than respiratory tract infected participants 5±3 ng/mL. 49% children were males and 52% were females. The vitamin D level was shown association with upper, lower and recurrent lower respiratory tract infections by showing p<0.05. The most commonly found symptom was common cold, and pneumonia in upper, lower, and recurrent lower respiratory tract infection, respectively whereas, insignificant findings were observed between vitamin D with age and gender by showing p>0.05.Conclusion: Vitamin D shown association with the incidence of respiratory in children of Peshawar